Model Quantum Writing Dengan Strategi PAILKEM Berbasis Vokasional Dalam Pembelajaran Menulis Karya Ilmiah - Sahli (ISLAMICA, 2017)
The skill of writing scientific papers (abbreviated MKI) among students is very less. Writing learning model used today is still conventional with the support of handbook (hand-out) is still thick with textbook style. The steps, including the giving of theory, practice or assignment, and the presentation of papers. Judging from the newly achieved target types, the acquisition of new students' knowledge reaches the declarative level (to know what) and procedural knowledge (to know how). However, the contextual knowledge (when and how) has not been touched. Similarly, when viewed from the side of learning objectives, the ability of students seems to be limited to knowledge of verbal information and intellectual skills. Based on this background, this study aims to develop alternative models of learning to write scientific papers that are more creative, innovative, interesting, and fun for students. The model in question is a Quantum Writing Model with Vocational-Based PAILKEM Strategy. Furthermore, this model is applied and developed in Islamic High School (STAI) Siliwangi Bandung. The indicator of the success of the process appears in the activity and diligence of students in carrying out the stages of the activities of writing scientific papers with this model. The indicator of the success of the results appears in improving the quality of students' scientific papers, both on the content aspect/substance and mechanical aspects (spelling and grammar).